Pengaruh Medan Elektromagnetik Extremely Low Frequency (ELF) Terhadap Kelistrikan Jantung - Muzayyadah, Vivian; Sudarti, Sudarti; Yushardi, Yushardi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Extreme low frequency (ELF) electromagnetic fields are a type of non-ionizing radiation produced by various electrical devices and infrastructure. Research has shown that exposure to ELF fields can affect the body's physiological functions, including the electrical activity of the heart. Exposure to extreme low frequency (ELF) electromagnetic fields has long been of concern due to its potential effects on human health. One area of ​​research focus is the effect of ELF exposure on the electrical activity of the heart. This study aims to conduct a systematic literature review regarding the impact of exposure to ELF fields on the characteristics of electrocardiogram (ECG) signals as an indicator of heart function. The research method used is a literature review by collecting and analyzing relevant scientific articles from various databases. The search was carried out using keywords related to ELF field, exposure, and cardiac activity. Articles that met the inclusion criteria were then reviewed in depth to identify patterns and trends in research findings. The results of the literature review show that exposure to ELF fields can influence several important parameters in the ECG signal, such as heart rate, QT interval, and heart rate variability.